Indústria e território no Brasil: desenvolvimento regional e divisão interna do trabalho industrial no Brasil entre 1995 e 2015 - Silva, Danilo Severian da (2019)
The period from 1930 to 1980 is marked by profound transformations in the Brazilian productive structure, where the mode of production of goods assumes the fully capitalist form with the predominance of the interests of industrial capital. For historical reasons, this found its lócus in the Center-South region of the country - more specifically in São Paulo -, subordinating the other regions to the same operative logic, which by politically and economically integrating the country, disarticulated other formations of a regional character - taking the region here as a particular form of material reproduction of life, with its own cultural codes and ways of subordination and domination of groups or classes. The production and reproduction of value, which started to be guided by an internal realization, as opposed to primary-export capital, implied a regional re-division of labor which meant for some regions of the country, such as the Northeast, a regression of its bases and economic development. In this way, the so-called "import substitution" process, which consolidated the industrial bourgeoisie not only in economic but also political domains, was aimed at reducing the external vulnerability resulting from unequal relations between the central and peripheral countries, diagnosis of Raul Prebisch ahead of the Economic Commission for Latin America and the Caribbean (ECLAC-UN). However, in an ambiguous way, this process ended up reproducing inequalities in the internal territory - as pointed out in the report of the Grupo de Trabalho para o Desenvolvimento do Nordeste, which was the basis for the creation of the Superintendency for the Development of the Northeast (Sudene). The inequalities in economic growth and income manifested territorially raised deep concerns of public planners, but an effective process of productive deconcentration only began to occur from the 1970s, when the State of São Paulo found itself losing relative position in industrial growth , reducing its share in the product, although still growing at high rates. This process occurred both through the phenomenon of agglomeration diseconomies, which began to exert centrifugal pressures on the locational decisions of the companies, as well as the increase of productive units, resulting from the active and coordinated action of the State, which acted to integrate the regions inter-regionally. industry links. In the 1980s, with the severe economic crisis triggered by the "debt crisis", the virtuous effects of productive deconcentration cooled down, with the state losing its leading role due to the contingencies imposed by hyperinflation and bleeding in the balance of payments. In this way, the Brazilian economy began to experience an erratic trajectory, with serious repercussions on both industry and regions. As an instrument of identification of the continuity or not of the productive deconcentration process, the concept of Relevant Industrial Agglomerations has an important role as an indicator of the locational tendencies of the industry, being used in this dissertation for a reading of the territorial deconcentration of the sector between 1995 and 2015